One-step surface functionalization of hydrogel-based, stimulus-responsive 3D microstructures for human stem cells - Munding, Natalie; Schlagheck, Christina; Wittbrodt, Joachim; Ho, Anthony Dick; Takashima, Yoshinori; Tanaka, Motomu (ACS applied materials & interfaces, 2025)
To regulate the maintenance and differentiation of stem and progenitor cells, a variety of hydrogels have been developed and applied as two-dimensional (2D) cell culture substrates that can provide well-defined mechanical cues by adjusting the stiffness. Recently, cell-laden hydrogels have been drawing attention as the three-dimensional (3D) cellular environments that can be patterned or printed by extrusion of the cell-polymer mixtures. Hydrogels also serve as 3D microstructures that can stimulate cells both mechanically and geometrically. For flexible, modular functionalization, the coupling of different extracellular matrix (ECM) proteins to side walls and curved surfaces is necessary. However, widely used heterobifunctional photo-cross-linkers encounter a problem because the light cannot reach into the scaffolds uniformly. In this study, we overcame this problem by integrating monomers with N-hydroxysuccinimide (NHS) groups into the copolymer hydrogels with tunable stiffness via careful adjustment of solvent miscibility. This enabled one-step surface functionalization with extracellular matrix proteins such as fibronectin, laminin, and gelatin, replacing photoactivation or laborious multistep functionalization. On the 2D hydrogel substrates functionalized with fibronectin, we found that more than 80% of human mesenchymal stem cells (hMSCs) were viable, and about 60% of them maintained proliferation capacity. These data confirmed that the introduction of NHS monomers caused no cytotoxic effect. We further designed and fabricated 3D microstructures containing various wall and bottom architectures using 3D printed stamps. The uniform functionalization of side walls and bottom surfaces with ECM proteins enabled us to accommodate hMSCs inside the 3D scaffolds, which was in stark contrast to commonly used photo-cross-linkers. The 3D scaffolds showed reversible swelling and deswelling by the addition and removal of soluble guest molecules in the presence of hMSCs, suggesting that the one-step functionalization method established in this study can be applied for a variety of hydrogel-based 3D microstructures for various cell types.
Online veröffentlicht: 5. Juni 2025
Gesehen am 12.09.2025